2016
DOI: 10.1681/asn.2014070679
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Endothelial-to-Mesenchymal Transition

Abstract: Antibody-mediated rejection (ABMR) is a leading cause of allograft loss. Treatment efficacy depends on accurate diagnosis at an early stage. However, sensitive and reliable markers of antibody-endothelium interaction during ABMR are not available for routine use. Using immunohistochemistry, we retrospectively studied the diagnostic value of three markers of endothelial-to-mesenchymal transition (EndMT), fascin1, vimentin, and heat shock protein 47, for ABMR in 53 renal transplant biopsy specimens, including 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
6
28
0
Order By: Relevance
“…The implantation biopsy specimen demonstrated no tubular vimentin expression that increased significantly in proximal tubules by postoperative day 2. Because IRI increases vimentin expression of tubular epithelial and endothelial cells, [5][6][7][8] we speculate that the confluence of vimentin exposed by IRI and constitutive vimentin expression, in the setting of pre-existing AVAs, triggered an acute AMR in our patient. Notably, treatment with antithymocyte globulin/ plasmapheresis/intravenous immunoglobulin resulted in clinical and histopathologic improvement with a concurrent decrease in tubular vimentin expression on follow-up biopsies.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The implantation biopsy specimen demonstrated no tubular vimentin expression that increased significantly in proximal tubules by postoperative day 2. Because IRI increases vimentin expression of tubular epithelial and endothelial cells, [5][6][7][8] we speculate that the confluence of vimentin exposed by IRI and constitutive vimentin expression, in the setting of pre-existing AVAs, triggered an acute AMR in our patient. Notably, treatment with antithymocyte globulin/ plasmapheresis/intravenous immunoglobulin resulted in clinical and histopathologic improvement with a concurrent decrease in tubular vimentin expression on follow-up biopsies.…”
Section: Discussionmentioning
confidence: 78%
“…4,10,16,17 Global production of vimentin throughout the kidney and its exposure to the immune system increase in response to apoptosis and endothelial injury, such as occurs during peritransplantation IRI or after rejection. [5][6][7][8] AVA is associated with focal proximal tubular vimentin expression and subclinical rejection by 21 days after kidney transplantation in rhesus monkeys. 18 In kidney transplantation in humans, increased AVA titers and IgG AVAs may be associated with the development of transplant glomerulopathy and interstitial fibrosis/tubular atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that PV-1 and caveolin-1 expression were a distinct feature of chronic rejection-induced transplant glomerulopathy and capillaropathy, respectively [37][38][39]. More recent data showed that three markers of endothelial-tomesenchymal transition (EndMT), fascin1, vimentin, and heat shock protein 47 provide a sensitive and reliable diagnostic tool for detecting endothelial activation during ABMR [40].…”
Section: Characteristic Histological Manifestations Of Chronic Abmrmentioning
confidence: 99%